2015
DOI: 10.1017/s1479262115000258
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering population structure and diversity inLuffa cylindrica(L.) M. Roem. using morphological and sequence-related amplified polymorphism markers

Abstract: Luffa cylindrica (L.) M. Roem. is an underutilized vegetable and a potential biodiesel crop for future. Its fruits are edible and used as vegetable. To aid in the selection of lines for breeding, genetic variation and structure of ten populations of L. cylindrica were determined with three morphological characters and 23 sequence-related amplified polymorphism (SRAP) markers. All the three morphological characters were found diverse among 45 accessions. The SRAP primers produced a total of 177 bands, out of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(25 reference statements)
1
1
0
1
Order By: Relevance
“…Overall, the genetic background of sponge gourd is inferred narrow in the present study. These results are in agreement with other studies, which concluded moderate genetic variation in sponge gourd (Tyagi et al 2016;Marr et al 2005). But incongruence was found with others who reported high genetic diversity (Rathod et al 2015;Prakash et al 2014;Junhui and Changping 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, the genetic background of sponge gourd is inferred narrow in the present study. These results are in agreement with other studies, which concluded moderate genetic variation in sponge gourd (Tyagi et al 2016;Marr et al 2005). But incongruence was found with others who reported high genetic diversity (Rathod et al 2015;Prakash et al 2014;Junhui and Changping 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, there is a need of more polymorphic markers. Earlier investigations have been conducted to illustrate the genetic variability of Luffa based on morphological variability (Prakash et al 2013), molecular markers such as RAPD (Hoque and Rabbani 2009), morphological and RAPD (Junhui and Changping 2008), SSR and SRAP (Jun et al 2010), morphological and SRAP (Tyagi et al 2016), RAPD and ISSR (Rathod et al 2015), morphological, ISSR and DAMD (Misra et al 2017) and SSR (Pandey et al 2017). To date, no data is available on comparative evaluation of genetic variability within sponge gourd using ISSR, SCoT and morphological markers.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, studies have been carried out in India to highlight the genetic diversity of Luffa based on morphological data and molecular markers (13)(14)(15)(16)(17)(18)(19). Luffa cylindrica has chemicals that affect hypersensitive reactions, act as immunostimulants, antiinflammatories, and participate in glycosidase activity.…”
Section: Introductionmentioning
confidence: 99%
“…Além do seu uso medicinal, as pesquisas atualmente conduzidas com a espécie avaliam principalmente as propriedades térmicas, mecânicas e químicas de suas fibras (GHALI et al, 2011;TANOBE et al, 2014). São poucos os trabalhos que geram conhecimento da variação genética em espécies do gênero (TYAGI et al, 2015), havendo a necessidade de estudos sobre a diversidade genética em acessos distanciados geograficamente, o que iria auxiliar na descoberta de possíveis amostras com potencial diferenciado para a agroindústria e fontes de genes de interesse para programas de melhoramento (PRAKASH et al, 2014).…”
Section: Introductionunclassified